Potential deleveraging in the German banking system and effects on financial stability - Manuel Pelzer; Nataliya Barasinska; Manuel Buchholz; Sören Friedrich; Sebastian Geiger; Nikolay Hristov; Philip Jamaldeen; Axel Löffler; Marcel Madjarac; Markus Roth; Leonid Silbermann; Lui-Hsian Wong (Deutsche Bundesbank, 2021)
The stability of the German banking system, in its capacity as an integral component of the country's financial system, has come under particular scrutiny, not least since the onset of the COVID-19 pandemic. Financial stability hinges on whether banks are sufficiently resilient to stress effects, which can arise if the economy suffers an unexpected downturn, for example. This might coincide with system-wide deleveraging if banks are insufficiently resilient. Systemwide deleveraging, in turn, could pose a risk to financial stability and have adverse repercussions for the real economy. The monitoring tool presented in this paper can be used to determine the potential deleveraging based on a sequence of six analytical steps that take multiple first-round scenarios into account. The sequence comprises (i) the loss-absorbing capacity of banks in the current (starting) situation, (ii) the banking system's key stress channels, (iii) deleveraging as a bank response to a reduction in their loss-absorbing capacity, (iv) second-round effects in the interbank market, and (v) the resulting effects on lending capacity to non-financial corporations, allowing for substitution effects. To illustrate the role played by macroprudential buffers, the scenarios initially assume that banks use their buffers. That is to say, banks tolerate undershooting the macroprudential buffer requirements and attempt to maintain their supply of credit. As a next step, a comparison is then made with the results if banks do not use their buffers. This comparison allows us, last of all, (vi) to estimate the macroeconomic effect of buffer use on the real economy. The results produced by the monitoring tool indicate that buffer use involves a macroeconomic trade-off. Given a (slightly) higher probability of default and spells of lower resilience, banks have to restrict their lending to a lesser extent, which allows an additional downturn in real GDP to be avoided. – – Nicht zuletzt nach Ausbruch der Covid-19-Pandemie stand die Stabilität des deutschen Bankensystems als integraler Bestandteil des nationalen Finanzsystems unter besonderer Beobachtung. Entscheidend für die Finanzstabilität ist die Frage, ob die Banken ausreichend gegen Stresseffekte abgesichert sind. Diese können sich ergeben, wenn beispielsweise die Wirtschaft unerwartet einbricht. Sollten Banken nicht ausreichend widerstandsfähig sein, könnte dies mit einem systemweiten Deleveraging einhergehen. Dies könnte wiederum Risiken für die Finanzstabilität bergen und negative Folgen für die Realwirtschaft mit sich bringen. In diesem Monitoring-Tool wird das Deleveraging-Potenzial mittels einer Sequenz von sechs Analyseschritten ermittelt unter Berücksichtigung mehrerer Erstrunden-Szenarien. Die Sequenz umfasst (i) die Verlustabsorptionsfähigkeit der Banken in der Ausgangslage, (ii) die wichtigsten Stresskanäle für das Bankensystem, (iii) Deleveraging als Reaktion der Banken, wenn ihre Verlustabsorptionsfähigkeit reduziert wird, (iv) Zweitrundeneffekte im Interbankenmarkt und (v) daraus resultierende Effekte auf die Kreditvergabekapazität an nichtfinanzielle Unternehmen unter Berücksichtigung von Substitutionseffekten. Um die Bedeutung makroprudenzieller Puffer aufzuzeigen, wird in den Szenarien zunächst angenommen, dass Banken ihre Puffer nutzen. Das heißt, dass Banken ein Unterschreiten der makroprudenziellen Pufferanforderungen akzeptieren und versuchen ihre Kreditvergabe aufrechtzuerhalten. Dies wird anschließend mit den Ergebnissen verglichen, wenn Banken ihre Puffer nicht nutzen. Aus diesem Vergleich kann zuletzt (vi) der realwirtschaftliche makroökonomische Effekt der Nutzung von Puffern auf die Realwirtschaft abgeschätzt werden. Die Ergebnisse des Monitoring-Tools zeigen, dass es zu einem gesamtwirtschaftlichen Trade-Off der Puffernutzung kommt: Bei einer (geringfügig) höheren Ausfallwahrscheinlichkeit und zeitweise geringerer Widerstandsfähigkeit müssen die Banken ihre Kreditvergabe weniger stark einschränken, wodurch ein zusätzlicher Einbruch des realen BIP vermieden werden kann.
Keywords: G01; G21; G28; 330; Financial Crises; Banks; Government Policy and Regulation